The dead march : a history of the Mexican-American War - Guardino, Peter, 1963- (Harvard University Press, 2017)
The bloody 1846-1848 war between the United States and Mexico filled out the shape of the continental United States, forcing Mexico to recognize its loss of Texas and give up the rest of what became the Southwestern United States. Generally people argue that the United States won this war because unlike Mexico it was already a unified nation that commanded the loyalty of its citizens. Focusing on the vivid experiences of ordinary soldiers and civilians, both Americans and Mexicans, The Dead March reveals something very different. The United States won not because it was more unified but instead because it was much wealthier. Both Americans and Mexicans had complicated relationships with their nations, relationships entangled with their commitments to their religions, their neighbors, and their families. The war's events, both on the grand scale of the conflict between nations and the more intimate scale of campaigns and battles, cannot be understood without probing this social and cultural history. Politicians could not simply conjure up armies, and generals could not manipulate units as if their members were chess pieces without ideas or attitudes. This book also uses the war to compare the two countries as they existed in 1846. The results of this comparison are quite startling. The United States and Mexico were much more alike than they were different, and both nations were still in the tumultuous and often violent process of constituting themselves. What separated them was not some fabled American unity or democracy but the very real economic advantages of the United States.--